Magic Strategies: the basic biology of multilevel, multiscale, health promotion - Wallace, Rodrick; Wallace, Deborah (PeerJ PrePrints, 2013)
A survey of the cultural psychology and related literatures suggests that Western biomedicine's fascination with atomistic, individual-oriented, interventions is a cultural artifact that may have little consonance with complex, subtle, multiscale, multilevel, social, ecological, or biological realities. Other cultural traditions may, in fact, view atomistic strategies as inherently unreal. A contrary perspective - similar to that of health promotion - suggests that the most effective medical or public health interventions must be analogously patterned across scale and level of organization: 'magic strategies' will almost always be synergistically - and often emergently - more effective than 'magic bullets'. The result can be formally derived in a relatively straightforward manner using an adaptation of the Black-Scholes economietric model, applied here to the metabolic cost of bioregulation under uncertainty. Multifactorial interventions focused at the human 'keystone' ecosystem level of mesoscale social and geographic groupings may be particularly effective. The analysis indicates that there is unlikely to be much in the way of 'simple' chronic disease. That is, serious comorbidity is usually inevitable, and may often be a consequence of therapeutic intervention itself. Study suggests that pairing of medical and prevention strategies with appropriate mesoscale neighborhood/social network interventions would: (1) Damp down unwanted treatment side effects. (2) Make the therapeutic alliance between practitioner and patient more effective. (3) Improve patient compliance. (4) Enhance placebo effect. (5) In the context of real stress reduction, synergistically improve the actual biological impacts of medical interventions or prevention strategies.
Keywords: rate distortion; regulation; social network; stability; uncertainty